exploring materiality disclosures in non-financial reporting evidence from annual reports in Eu companies - Weitzel, Paulina Zara (2022)
Non-financial materiality is anew, vague concept that comes with many uncertainties in its application, leading to reports likely lacking objectiveness, reliability, and comparability. This work investigates materiality disclosures in non-financial reports from Euro Stoxx 50 listed companies in 2020, seeking insights in to the status quo of reporting harmonization. Findings suggest that materiality disclosures in non-financial reporting are of great disparity. While legal environment and industry do not influence the degree of non-financial materiality disclosure, the choice of reporting framework does. Therefore ,to increase reports’ usability, it is recommended tothe standard setter to develop a common reporting standard.